Studi Literatur Sistem Elektrokultur Dalam Mempercepat Pertumbuhan Dan Perkembangan Tanaman - Ahmad Jahrudin; Siti Ayu Kumala (Jurnal Riset Fisika Indonesia, 2024)
In the development of agricultural or plant technology, innovations are needed to increase efficiency in the process of accelerating growth and the harvest period. The application of physics in the fields of agriculture and biology is one that can be developed. One study that is very interesting to discuss is the application of the electroculture system, which uses electricity to help speed up the growth process and harvest period, in addition to growth and development of electroculture is also claimed to be able to minimize attacks by insect pests and viruses, in this article we review several studies related to the effect of the electroculture system on plants, and from several studies we can prove the effect of applying the electroculture system in accelerating the growth and development process, there are several ways to Electroculture applications include antenna systems, direct current, alternating current, development of electrogenetic seeds and the use of electrolysis